"Be Strong and Resolute!": Reading Joshua in the Contemporary Church. Issue 1 (December 2015) - Sharp, Carolyn J.
The Lord spoke to Joshua son of Nun, Moses' assistant, saying, "My servant Moses is dead. Now proceed to cross the Jordan, you and all this people, into the land that I am giving to them, to the Israelites…. Be strong and resolute; do not be frightened or dismayed, for the Lord your God is with you wherever you go." (Joshua 1:1–2, 9)